The effects of climate change on mental health and psychological well-being: Impacts and priority actions - Shazia Soomro; Dianen Zhou; Iftikhar Ahmed Charan (Cambridge Prisms: Global Mental Health)
Climate anxiety has a negative impact on the mental health and psychological well-being of the vulnerable population. The goal is to assess many factors that affect mental health and psychological well-being, as well as how climate change affects mental health in Pakistan’s vulnerable population. This study provides evidence-based insights into the long- and medium-term impacts of extreme weather events on mental health. To obtain information on these variables, this research uses a quantitative approach and a cross-sectional survey design with a multivariate regression model for empirical tests on a sample of parents and children with an impact on mental health from climate change anxiety. Results indicate that individuals who experience shock climate change anxiety and its effects on mental health and psychological well-being. Climate change can have detrimental effects on children’s mental health. (1) Children’s Stress Index (CSI): (2) climate change anxiety (CCA), (3) generalised anxiety disorder (GAD) and (4) major depression disorder (MDD), as reported by the children with mental health outcomes. The findings of this study show that climate change has a stressful effect on mental health. The article concludes with a discussion on strategies to address the anticipated mental health issues among children due to climate change.